Implementation And Characterization Of Power Amplifier Asing RF Test Board - Hj Othman, Azzah (Universiti Sains Malaysia, 2006)
Power amplifier is a part of RF front-end transmitter block. Usually, it is located at the end of the transmitter. In a wireless system, RF power amplifier is need at the end of the circuit so that the signals transmitted effectively. Power amplifier will amplify the power as high as it could so that it can cross a certain distance specify. Power delivered to the antenna act as a 50Ω load. The output power of the power amplifier can reach until a few mili-watts for a small network and a few hundreds-watts for a large network.